Negative expectations (nocebo phenomenon) in clinical interventions: A scoping review - Hamid Nasiri-Dehsorkhi; Shahram Vaziri; Ahmad Esmaillzadeh; Peyman Adibi (Wolters Kluwer Medknow Publications, 2024)
Unpredictable, undesirable, and confusing reactions in the face of psychological or medical interventions make the clinical presentation more complicated and may represent clinically unexplained symptoms and also disturbed the doctor-patients relationship and decrease patients' benefits of treatment. It seems that negative expectations from the treatment (nocebo phenomenon) can explain such reactions. The aim of the current study is a scoping review and investigate different aspects of the nocebo phenomenon (negative expectations) in clinical interventions. This paper follows a scoping review of the existence, importance, and multidimensions of the nocebo phenomenon in medical and psychological interventions. Data sources include literature databases (ProQuest, PubMed, Google Scholar, and Scopus) reviewed from inception dates to 2023, and the terms negative expectations, nocebo effect, placebo effect, negative placebo, and clinical interventions were searched. The review of the available articles showed that negative expectations play an important role in the process and effectiveness of clinical interventions. Negative expectations (here named nocebo effect) can significantly interfere with rapport and treatment processes. Some underlying components of the nocebo effect include negative expectancies, conditioning, social learning, memory, cognitive distortions, meaning, motivation, somatic focus, negative reinforcements, personality, anxiety, and neurophysiological factors such as CCK, dopamine, and cortisol are proposed for development and presence of nocebo phenomenon in clinical practice. Negative expectations with its biopsychosocial aspects play an important and amazing role in disorganizing medical and psychological interventions. Using appropriate methods to reduce nocebo effects in therapeutic interventions may increase treatment compliance and adherence and increase the effectiveness of interventions.